Successful outcome of a pregnancy derived from premature ovulation in a gonadotropin‐releasing hormone antagonist protocol: A case report. Issue 2 (22nd December 2020) - Inoue, Daichi; Asada, Yoshimasa; Ando, Tomoko
Abstract: In the gonadotropin‐releasing hormone (GnRH) antagonist protocol, it is necessary to reinforce contraceptive guidance assuming that luteinizing hormone surge is not detected by measurement of serum level and ovulation is not suppressed by GnRH antagonist. Abstract : In the gonadotropin‐releasing hormone (GnRH) antagonist protocol, it is necessary to reinforce contraceptive guidance assuming that luteinizing hormone surge is not detected by measurement of serum level and ovulation is not suppressed by GnRH antagonist.